3, 14-Bis(4-formylphenyl)-17, 17-di(n-pentyl)tetrabenzo[a, c, g, i]fluorene showing solvatochromism and crystallochromism in fluorescence. Issue 8 (23rd February 2017) - Ueki, Masanori; Kimura, Yusuke; Yamamoto, Yuma; Nishida, Jun-ich; Kitamura, Chitoshi; Tanaka, Mirai; Ikeda, Hiroshi; Kawase, Takeshi
Abstract: The substituent effect on optical properties of 3, 14-diphenyl-17, 17-di( n -pentyl)tetrabenzofluorene derivatives bearing electron-withdrawing groups (NC, CH3 OCO, CH3 SO2, and OHC) at 4-position of the phenyl groups were investigated. These compounds were readily prepared by using Suzuki–Miyaura cross-coupling as a key step. The 4-cyano, 4-methoxycarbonyl, and 4-methylsulfonyl derivatives display intense blue to blue-green fluorescence in CH2 Cl2 and in the solid states. On the other hand, the title compound forms two polymorphs, and thus, exhibit crystallochromism in fluorescence; the prismatic crystal emits intense yellow fluorescence, and the other crystal form does blue-green fluorescence. Moreover, the compound shows large solvatofluorochromism (Δ λ EM  = 67 nm). The crystallographic analysis of the prismatic crystal reveals that the tetrabenzofluorene moiety of the compound possesses a helical structure with a C 2 symmetry and the molecules form a herringbone-like structure. The density function theory calculations predict the remarkable intramolecular charge-transfer character of the compound. The prediction is in good agreement with the observed fluorescence properties. Graphical abstract: